PENGARUH KINERJA LINGKUNGAN DAN KINERJA SOSIALTERHADAP KINERJA KEUANGAN DI INDONESIA: Studi pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2019-2020 - Ricky Dewangga Putra Nugraha, - (2023)
The purpose of this research is to analyze the effect of social performance and environmental performance on the financial performance of manufacturing firm in Indonesia. The social Sustainability Report Disclosure Index (SRDI) is used as the proxy for social performance, the environmental SRDI for environmental performance, and the Return On Assets (ROA) ratio for financial performance. To calculate SRDI, the author refers to the Global Reporting Initiative (GRI) Standard.The research method used is the descriptive-quantitative method. In this research, the data population is all manufacturing firms listed on the Indonesian Stock Exchange (IDX) for the years 2019-2020. From this population, some samples are taken using the purposive sampling method.The finding shows that simultaneously, both variables have no significant effect on the financial performance of the manufacturing firms in Indonesia. Partially, the social performance variable has no significant effect on the financial performance of the manufacturing firms in Indonesia. Partially, the environmental performance variable has no significant effect on the financial performance of the manufacturing firms in Indonesia. Simultaneously, both variables have no significant effect on the financial performance of the manufacturing firms in Indonesia. Keyword: Social Performance, Environmental Performance Financial Performance, Sustainability Report Disclosure Index (SRDI), Return On Assets (ROA).